1993
DOI: 10.1200/jco.1993.11.4.726
|View full text |Cite
|
Sign up to set email alerts
|

Anti-B4-blocked ricin: a phase I trial of 7-day continuous infusion in patients with B-cell neoplasms.

Abstract: Anti-B4-bR can be administered safely by 7-day continuous infusion with tolerable, reversible toxicities to patients with relapsed B-cell neoplasms. Although occasional responses were seen, future trials will use anti-B4-bR in patients with lower tumor burdens to circumvent the obstacle of immunotoxin delivery to bulk disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(40 citation statements)
references
References 11 publications
0
39
0
1
Order By: Relevance
“…Another phase I trial of continuous infusion administration was conducted on 43 patients of B-cell neoplasms. In this trial, reported in 1993, two complete remissions and two partial remissions were observed [117]. Unfortunately, the following phase II trial, conducted on 16 NHL patients did not show any objective response.…”
Section: Anti-b4-brmentioning
confidence: 73%
“…Another phase I trial of continuous infusion administration was conducted on 43 patients of B-cell neoplasms. In this trial, reported in 1993, two complete remissions and two partial remissions were observed [117]. Unfortunately, the following phase II trial, conducted on 16 NHL patients did not show any objective response.…”
Section: Anti-b4-brmentioning
confidence: 73%
“…Although early studies showed that unmodified anti-CD19 antibodies induced B-cell depletion, their clinical efficacy was limited (8,15), and consequently, clinical trials focused on anti-CD19 immunotoxin conjugates (10,39). To maximize the cytotoxic potential of an unmodified antibody, multiple modes of tumor cell killing must be engaged: immune effector function (ADCC, ADCP, or CDC) and growth inhibition mechanisms (apoptosis or cell cycle arrest).…”
Section: Discussionmentioning
confidence: 99%
“…CD19 has been a focus of immunotherapy development for over 20 years, and several CD19-specific antibodies have been evaluated for the treatment of B-lineage malignancies in vitro, in mouse models, and in clinical trials. These have included unmodified anti-CD19 antibodies (8,9), antibody-drug conjugates (10)(11)(12), and bispecific antibodies targeting CD19 and CD3 (13) or CD16 (14) to engage cytotoxic lymphocyte effector functions. Although early clinical studies with murine unconjugated CD19 antibodies showed safety and responses in individual patients, these responses were not durable (15).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 90% of patients with epithelial carcinomas and 30% of the lymphoma patients have detectable human antimouse antibody and human antitoxin antibody after one cycle of immunotoxin therapy (1)(2)(3)(4). Although the formation of human antimouse antibody can be partly overcome by the use of humanized or chimeric monoclonal antibodies, the formation of antitoxin antibodies continues to represent a major problem.…”
Section: Introductionmentioning
confidence: 99%